Analysis of Renewable Energy Directive II on Trading of Indonesian Palm Oil Associated with the GATT - Amanda Fadhilla Chairunisa; Imam Haryanto (Universitas Airlangga, 2021)
International economic relations and the policies that regulate them are important for countries. In this study, the authors analyse how the Renewable Energy Directive (RED) II policy, a derivative of the European Union's (EU) RED policy, will affect the Indonesian palm oil trade. It also examines the violations of previous policies, including the General Agreement on Tariffs and Trades (GATT). The authors show that the GATT regulates how international trade relations should be carried out, and any violations of this international agreement could affect economic relations between the two countries on micro and macro scales. The authors adopt normative juridical methods for the study, basing their legal research on library and secondary materials. This study reflects on how RED II can affect trade in Indonesian palm oil products. When RED II went into effect in 2021, the EU violated the nondiscrimination principle in GATT 1947.